(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study examined the effective implementation of Gorumudda Scheme in Primary Schools of Visakhapatnam district. Various Indian and foreign studies were reviewed. Descriptive Survey method has been used in this study. The purpose of this Gorumudda scheme is to provide attracting children from disadvantaged sections to school, improving regularity, nutritional services, socialization benefits, and benefits to women are some that got highlighted to improve the quality of education in the state. The sample consists of 100 parents of children studying in Primary Schools of Visakhapatnam district. The investigator used stratified random sampling technique for selecting the sample. Questionnaire was constructed for the parents to find out the opinions on the Implementation of Gorudmudda (Mid Day Meal) Scheme in Primary Schools of Visakhapatnam District. The data were analyzed using various statistical methods like mean, SD, ’t’ test and F-test were the statistical techniques used. The score obtained by different groups are compared across the variables like gender, age, educational status, Annual Income, caste and religion. The results were found that, there is a significant difference among the perceptions of parents according to their demographic variables i.e., gender, age, educational status, Annual Income, caste and religion. The results are discussed in light of previous research studied; suggestions and Recommendations for further research were also suggested.